MicroRNAs and Long Non-Coding RNAs as Regulators of NANOG Expression in the Development of Oral Squamous Cell Carcinoma - Grubelnik, Gašper; Boštjančič, Emanuela; Aničin, Aleksandar; Dovšak, Tadej; Zidar, Nina (Frontiers in Oncology, 2021)
NANOG is a stem cell transcription factor that is believed to play an important role in the development of oral squamous cell carcinoma (OSCC), but there is limited data regarding the role of long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) in the regulation of NANOG expression. We therefore analyzed expression of NANOG, NANOG-regulating miRNAs and lncRNAs in OSCC cancerogenesis using oral biopsy samples from 66 patients including normal mucosa, dysplasia and OSCC. Expression analysis of NANOG, miR-34a, miR-145, RoR, SNHG1, AB209630 and TP53 was performed using qPCR and for NANOG protein detection, immunohistochemistry. NANOG protein showed no staining in normal mucosa, very weak in low-grade dysplasia and strong staining in high-grade dysplasia and OSCC. NANOG, miR-145, RoR and SNHG1 showed up-regulation, TP53 and miR-34a showed down-regulation and AB209630 showed variable expression during cancerogenesis. NANOG mRNA was up-regulated early in cancerogenesis, before strong protein expression can be detected. NANOG was in correlation with miR-145 and RoR. Our results suggest that miRNAs and lncRNAs, particularly miR-145 and RoR, might be important post-transcription regulatory mechanisms of NANOG in OSCC cancerogenesis. Furthermore, NANOG protein detection has a diagnostic potential for oral high-grade dysplasia, distinguishing it from low-grade dysplasia and non-neoplastic reactive lesions.